Professional anchorage and values related to work in Peru - Cabrera Echegaray, Susana (2017)
The purpose of this article is to reflect on why in Peru it is difficult for professionals to achieve their goals in organizations and why they cannot achieve loyalty to their employees. There are factors such as the rupture situation, between the studies performed and the occupation exercised; the lack of adaptation of the educational system to the needs of the productive apparatus; the prejudice of the employer on the formative provenance of its possible employee. Faced with this labor reality, organizations must recognize the importance of paying attention to human capital aligned with company strategies. Focusing on people, some have a clear potential to develop their professional skills and organizational environment conducive, but fail to achieve the expected professional deployment. In this sense, Schein's theory of career anchors, generates a new prospect, refers to the occupational self-concept that explains the development, stability, restrictions and integration of the worker's career and the theory of values related to the work of Schwartz, as factors that guide the decisions of the people, conditioning the time to choose their studies and develop a particular profession.